Phase unwrapping for SAR interferometry based on an ant colony optimization algorithm - Wei, Z.-Q.; Xu, F.; Jin, Y.-Q. (International journal of remote sensing, 2008)
Phase unwrapping is a key step in extracting digital elevation models (DEMs) from interferometric synthetic aperture radar (InSAR) data. A new two-dimensional (2-D) phase unwrapping algorithm based on ant colony optimization (ACO) is proposed, which is used to configure the shortest path linking all residues in an interferogram. Using an optimization strategy to establish the branch cuts, the unwrapping error can be significantly reduced. Simulated and real InSAR image datasets are studied to evaluate the performance of the algorithm. The results of the simulated datasets show that the errors of the algorithm are lower than some conventional methods, and the results from a real InSAR image dataset demonstrate that the ACO approach has no isolated regions in comparison with some conventional approaches. It indicates that our ACO algorithm is an optional compromise strategy between preferable phase unwrapping precision and time-consuming computation.